STANDARDS OF PROTECTION OF PRIVATE LIFE IN CRIMINAL INTELLIGENCE INVESTIGATIONS IN THE CASE LAW OF THE SUPREME COURT OF LITHUANIA - Aurelijus Gutauskas (Jurisprudencija)
This article focuses on applying the provisions of the Criminal Intelligence Law to detect criminal offences. Based on the recent case law of the Supreme Court of Lithuania, the author provides insights into the problematic aspects of the application of certain provisions of the Criminal Intelligence Law. It examines the extent to which the tools of criminal intelligence can legitimately invade a person’s private life. The conditions for provocation by criminal intelligence, the criteria for (non-)recognition of evidence collected by private individuals, the problems of establishing a factual basis for initiating a criminal intelligence investigation, and the nuances of the duration of non-public actions are discussed. The Code of Criminal Procedure does not regulate the conditions for the use in criminal proceedings of data obtained in the course of a criminal intelligence investigation; therefore, it is decided on a case-by-case basis, taking into account, inter alia, the case law of the Supreme Court of Lithuania, and whether the information obtained in the course of a criminal intelligence investigation meets the requirements for evidence set out in the Code.